2023
DOI: 10.1177/23743735231171564
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives of the Hospital Discharge Process: A Qualitative Study

Abstract: Care transitions after hospitalization require communication across care teams, patients, and caregivers. As part of a quality improvement initiative, we conducted qualitative interviews with a diverse group of 53 patients who were recently discharged from a hospitalization within a safety net hospital to explore how patient preferences were included in the hospital discharge process and differences in the hospital discharge experience by race/ethnicity. Four themes emerged from participants regarding desired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This in-depth analysis of patients’ experiences reinforces common challenges identified in the existing literature such as the lack of personalized information [ 9 11 ], loss of autonomy during hospitalization [ 14 , 74 , 75 ], difficulties in obtaining medication at discharge [ 11 , 45 , 76 ] and challenges in understanding treatment modifications and generics substitution [ 11 , 32 , 77 , 78 ]. Some of these studies were conducted during patients’ hospitalization [ 10 , 75 , 79 ] or up to 12 months after discharge [ 80 , 81 ], but most studies focused on the few days following hospital discharge [ 9 , 11 , 14 , 82 ]. Qualitative studies on medications at transition often focused on a specific topic, such as medication information, or a specific moment in time, and often included healthcare professionals, which muted patients’ voices [ 9 11 , 47 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This in-depth analysis of patients’ experiences reinforces common challenges identified in the existing literature such as the lack of personalized information [ 9 11 ], loss of autonomy during hospitalization [ 14 , 74 , 75 ], difficulties in obtaining medication at discharge [ 11 , 45 , 76 ] and challenges in understanding treatment modifications and generics substitution [ 11 , 32 , 77 , 78 ]. Some of these studies were conducted during patients’ hospitalization [ 10 , 75 , 79 ] or up to 12 months after discharge [ 80 , 81 ], but most studies focused on the few days following hospital discharge [ 9 , 11 , 14 , 82 ]. Qualitative studies on medications at transition often focused on a specific topic, such as medication information, or a specific moment in time, and often included healthcare professionals, which muted patients’ voices [ 9 11 , 47 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results provide a particularly thorough description of how participants move from a state of total dependency during hospitalization regarding their medication management to a sudden and complete autonomy after hospital discharge impacting medication management, understanding, and adherence in the first days after discharge for some participants. Several qualitative studies have described the lack of shared decision-making and the loss of patient autonomy during hospitalization, which had an impact on self-management and created conflicts with healthcare professionals [ 75 , 81 , 84 ]. Our study also highlights nuanced patient experiences, including varying levels of patient needs, involvement, and proactivity during hospitalization and outpatient care, and our results contribute to capturing different perspectives that contrast with some literature that often portrays patients as more passive recipients of care [ 14 , 15 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…They exhibit valuable qualities such as bedside manner, attentive listening to patients' voice, and a humanized continuing care and referral services, which help bridge this gap. Increasingly, academia is recognizing the importance of valuing patients' experiences and preferences in delivering high-quality care [42][43][44]. Attentive bedside manner and listening to patients allows healthcare providers to respond promptly to their urgent needs [45].…”
Section: Plos Onementioning
confidence: 99%
“…While understanding the vulnerabilities of diverse populations is important to targeting areas for intervention, so is recognizing strengths of these communities. Given the prominent role of family in many other cultures compared to the U.S. Qualitative evidence has shown that minoritized patients are more likely to feel that their needs and preferences were not considered in discharge planning (Jones et al, 2023). As such, best practices to understand patients' and families' preferences and values should be pursued as a strategy to promote engagement.…”
Section: Meaningful Involvement Of Patients and Their Families In The...mentioning
confidence: 99%